Subclavian-to-descending aortic bypass for the treatment of severe late-stage aortic coarctation in a 62-year-old adult: a case report and literature review - Wang, Bowen; Zhang, Zhan; Chen, Ke; Zhou, Xing; Gao, Fentang; Xie, Ping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAortic coarctation (CoA) is a congenital cardiovascular condition usually diagnosed in infancy or childhood. Cases in adults are rare and often go undetected because symptoms can be obscured by extensive collateral circulation.Case descriptionA 62-year-old male was admitted to Gansu Provincial Hospital in December 2024 with complaints of recurrent chest tightness, shortness of breath, blurred vision, and tinnitus persisting for over two months. Physical examination revealed significant blood pressure discrepancies between the upper and lower extremities (>50 mmHg). Imaging confirmed severe CoA with nearly complete interruption of the descending aorta, extensive collateral circulation, and complications, including hypertensive crisis with cerebral hemorrhage likely due to extreme hypertension, and bronchiectasis with active pulmonary infection. After multidisciplinary team evaluation, left subclavian artery-to-descending aorta bypass grafting was performed. Postoperatively, blood pressure normalized across all limbs, and the patient remained asymptomatic at the six-month follow-up, with patent graft flow.ConclusionThis case of severe CoA in a 62-year-old male highlights the importance of early recognition of atypical presentations in adult patients, the need for individualized surgical strategies, and the benefits of long-term follow-up to ensure successful management and optimal outcomes.